The first case report of CODAS syndrome in Chinese population caused by two LONP1 pathogenic mutations - Tang, Yi; Liu, Yu-Xing; Sheng, Yue; Fan, Liang-Liang; Zhang, Ai-Qian; Zheng, Zhao-Fen (Frontiers in Genetics, 2023)
Background: CODAS syndrome (MIM 600373) is a multi-system developmental disorder characterized by cerebral, ocular, dental, auricular, and skeletal anomalies. Mutations in the LONP1 gene can contribute to CODAS syndrome, while the underlying molecular mechanisms requires further investigation. Method: We described a Chinese little boy who has suffered from cognition impairment, cataracts, caries, abnormal auricle and skeletal anomalies since birth. The patient’s parents are non-consanguineous and healthy. Whole-exome sequencing (WES) was employed to explore the genetic entity of this family. Results: A compound heterozygous missense mutation (NM_004793: c.2009C>T/p.A670V and c.2014C>T/p.R672C) of LONP1 was identified in the patient. Considering the clinical phenotypes and genetic results, the patient was diagnosed as CODAS syndrome. Conclusion: Here we reported the first case with CODAS syndrome in Chinese population. WES identified a compound heterozygous missense mutation of LONP1 gene in the patients. Our study not only provided data for genetic counseling and clinical diagnosis to this family, but also expanded the clinical spectrum of LONP1-related CODAS syndrome.